The Influence of Vygotsky's Learning Theory on the Critical Thinking Ability of Students of Elementary School Madrasah - Lubis, Melda Lestari; Amir, Mawaddah Aulia; Chandrawinata, Ramilah (Jurnal Pengabdian Nusantara, 2025)
Critical thinking skills are essential cognitive skills that need to be developed early on, especially at the elementary education level such as Islamic elementary schools (MI). This study aims to examine the influence of Vygotsky's learning theory on the development of critical thinking skills in MI students through the Systematic Literature Review (SLR) approach. Vygotsky's theory, which focuses on social interaction, scaffolding, and the Zone of Proximal Development (ZPD), has been shown to support the creation of collaborative learning that stimulates students' reasoning skills. The results of studies from various literatures in 2020–2024 show that learning approaches based on Vygotsky's theory, such as Problem Based Learning (PBL), guided inquiry, and learning communities, can significantly improve students' critical thinking skills. However, challenges such as limited teacher competence, high student-teacher ratios, and minimal contextual learning resources are obstacles to its implementation. Therefore, strengthening strategies that include teacher training, development of learning tools, and institutional support are crucial so that this theory can be applied effectively in the MI environment.